ヒガシ ナンキョク ドーム フジ ニオケル センソウ コア クッサク ト クッサクコウ ケーシング - 本山, 秀明; モトヤマ, ヒデアキ; 榎本, 浩之; エノモト, ヒロユキ; 宮原, 盛厚; ミヤハラ, モリヒロ; 渡辺, 興亜; ワタナベ, オキツグ; Motoyama, Hideaki; Enomoto, Hiroyuki; Miyahara, Morihiro; Watanabe, Okitsugu (1995)
P(論文) 東南極ドームふじにおける深層コア掘削計画が, 1992年から南極地域観測隊(JARE)によって行われている。JARE-34は, 1993年12月から1994年1月にかけて, ドームふじ観測拠点において112m深の浅層コア掘削と, 掘削孔のケーシングを実施した。雪の圧密過程は, みずほ高原の特性と一致した。氷切削の速度には, 氷の物理特性の情報が含まれている。 A Deep Ice Coring Project at Dome Fuji, East Antarctica has been conducted by the Japanese Antarctic Research Expedition (JARE) since 1992. Shallow ice coring of 112m in depth and casing of its borehole at Dome Fuji Station were carried out in December 1993 and January 1994 by JARE-34. The characteristics of snow densification showed similar features to those on Mizuho Plateau. The penetration rate of ice cutting can potentially provide useful information of physical properties of ice. departmental bulletin paper